SEBARAN KLOROFIL-a DI PERAIRAN PANTAI PADANG DAN PARIAMAN PROVINSI SUMATERA BARAT MENGGUNAKAN CITRA SATELIT AQUA MODIS - Fandi Handika Arta; Mubarak Mubarak; Syafruddin Nasution (Jurnal Ilmu Lingkungan, 2016)
This research was conducted in March 2016. Sampling was conducted in the coastal waters of Padang and Pariaman, West Sumatra. The purpose of this research is to map the distribution of chlorophyll-a in the coastal waters of Padang and Pariaman, West Sumatra Province. The method used in this research is survey method. The results of image analysis is known that the distribution of chlorophyll-a uniform occurred in February 2016 in which the distribution covers a large area and at least shades of difference in that month. Furthermore, the uneven distribution of chlorophyll-a occurred in November 2015 in which the distribution is so broad and it could be seen from striking differences in color gradation. Results of laboratory analysis known that the highest of chlorophyll-a concentration was occurred in the month of November 2015 and the lowest occurred in March 2015.